THE ABILITY OF PRODUCING ANECDOTIC TEXT THROUGH A SCIENTIFIC APPROACH TO VOCATIONAL SCHOOL STUDENTS OF MUHAMADIYAH MATARAM - Adha, Isna Dia'ul; Masnun, Masnun; Mahyudi, Johan (Universitas Hamzanwadi, 2020)
This research was conducted to see the extent to which students' abilities in producing anecdotal texts. The current pandemic state forces educators and students to carry out learning and learning activities through online or online schools, but this does not discourage researchers in seeing the extent to which students' ability to understand the steps in producing anecdotal texts through scientific methods. Researchers in this study act as listeners, and use the observing method, this research also includes qualitative research, where researchers see how educators provide material and assignments, then help examine the results of assignments produced by students to see the extent of students' abilities in producing anecdotal texts. This study provides the answer that online learning is difficult and face-to-face learning is better at helping students understand learning material. The results of this study, the ability of students in producing anecdotal texts through scientific methods is still low.Keywords: Text, Anecdotes, Methods, Scientific